UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN PENDEKATAN PAKEM PADA PELAJARAN MATEMATIKA - Teguh Santoso; Siti Muflihah; Yulia Putri Agtasari (MEGA: Jurnal Pendidikan Matematika, 2023)
Student learning outcomes are still not optimal because the methods and approaches used are less varied. The aim of this research is to improve mathematics learning outcomes using the PAKEM approach. This type of research is Classroom Action Research (PTK) which is carried out through cycles. Each cycle consists of planning, action, observation and reflection. Data collection instruments used in this study were tests and observations. The results of this study showed that the pre-cycle was 33.33% with complete student learning outcomes of 20%. Then in the first cycle the class average value was 56% with a complete learning achievement value of 40%. Then it was continued in cycle II which experienced an increase in class average of 85.33% with a completeness score of 93.3% (reaching a score of 60 and above as many as 14 students) in other words students were thorough in learning mathematics using the PAKEM approach method